Effectiveness of Reducing Ammonia Levels in Hospital Wastewater Using A Combination of Bagasse Bio Adsorbent and Nanofiltration Membrane - Laily Noor Fitri Lestari; Subriyer Nasir; Leily Nurul Komariah (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
The increasing environmental impact caused by hospital wastewater, particularly due to its ammonia content, necessitates innovative treatment methods. This study investigates the effectiveness of a combination of sugarcane bagasse-based activated carbon bio-adsorbent and nanofiltration membrane technology to reduce ammonia concentrations in hospital wastewater. The activated carbon was produced through carbonization at 550°C and chemical activation using 10% H2SO4. Adsorption experiments were conducted by varying bed heights (5, 7.5, and 10 cm) and flow rates (2, 3, and 4 L/min), followed by nanofiltration at 25, 30, and 35 Psi pressures. Results showed that the combined treatment reduced the wastewater pH from 9.08 to 6.53 and ammonia concentration from 4.61 mg/L to 0.02 mg/L, successfully meeting regulatory standards. This indicates that the integrated method effectively decreases ammonia levels and improves wastewater quality before discharge.